Components of the Hippo pathway cooperate with Nek2 kinase to regulate centrosome disjunction - Mardin, Balca; Kellner, Cornelia; Baxter, Joanne E.; Hardy, Tara; Scholz, Sebastian Richard; Fry, Andrew M.; Schiebel, Elmar (Nature cell biology, 2010)
The Nek2 kinase directs the separation of duplicated centrosomes. Now the Hippo pathway components hSav1 and Mst2 are shown to regulate the function of Nek2 at the centrosome. This pathway cooperates with the kinesin Eg5 to mediate centrosome separation.
Das PDF enthält zusätzlich einen Anhang von 12 Seiten
Gesehen am 04.05.2023